2017
DOI: 10.1016/j.nimb.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Mean excitation energies for molecular ions

Abstract: 2017-08-30T02:06:39

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…2-5). This conclusion is identical to what we have seen for non-confined hydrogen [15] as well as for dipole sum rules of a range of other non-confined atoms and molecules [39,40].…”
Section: Discussionsupporting
confidence: 90%
“…2-5). This conclusion is identical to what we have seen for non-confined hydrogen [15] as well as for dipole sum rules of a range of other non-confined atoms and molecules [39,40].…”
Section: Discussionsupporting
confidence: 90%
“…Sauer et al () computed the mean excitation energies of various atomic ions. Mean excitation energies of oxygen and sulfur ions have been computed for this study following the method detailed by Sauer et al () or Jensen et al () and are reported in Table .…”
Section: Modeling the Effect Of The Physical Processesmentioning
confidence: 99%
“…Based on our previous basis set studies, 3,5,15,16 we adopted the largest correlation-consistent basis sets of Dunning and co-workers 17 as one-electron basis sets. For B to F, Dunning's core-valence correlation consistent basis set aug-cc-pCV5Z was employed; for Al to Ar, the fully uncontracted aug-cc-pCV5Z was employed.…”
Section: Details Of the Calculationsmentioning
confidence: 99%
“…Thus, the stopping of heavy charged particles in matter is basically an electronic structure problem and application of known methods of electronic structure theory that are able to calculate all electronic excitation energies of a given atom or molecule may straightforwardly be applied to this problem. [2][3][4][5] The range of electronic excitation energies needed to calculate the mean excitation energy as well as many other sum-over-state molecular properties 6,7 includes both bound and continuum states, and for many properties, for all atoms and molecules, the major contribution to the mean excitation energy originates from electron excitations into the continuum. Luckily, it turns out that a stick-spectrum representation of the continuum in terms of pseudo-states placed in the continuum suffices when calculating atomic and molecular mean excitation energies, 8 which means that one may apply standard finite basis set methods also when calculating the continuum contributions to the mean excitation energies.…”
Section: Introductionmentioning
confidence: 99%